The adolescent´s brain: Coaching young athletes´ development - Finn, P. (Techniques Magazine, 2024)
The human brain continues to develop throughout adolescence and as the adolescent continues to learn, the pre-frontal lobes grow in size. This part of the brain, as has now been explained in many books, is responsible for, among other things, decision-making, planning, judging, maintaining attention and inhibition of impulses that may not be sicietally acceptable. In other words, the pre-frontal region is the Chief Executive Officer (CEO) of out brain. Quite interestingliy, as the adolescent continures to learn and develop the functions listed above, this prefrontal region initially grows and the begins to shrink. It shrinks as the nerves begin to prune their connections and as a result, become more efficient in processing information. So, to put it lightly, the CEO of the adolescent brain is dynamically growing and learning on the job. Research shows girls mature through this process up to two years sooner than boys. Most anyone who has worked with groups of young adolescents know that, in general, girls are typically more aware of the social context of their environment. They inhibit impulses more readily, display better organization and planning and are often more successful within structures like school where these traits are rewarded. In addition, the emotional center of the brain, known broadly as the libic system, generates a range of both simple and complex emotions. This system is located behind the pre-frontal area and has nerve pathways connecting them together. Simple emotions may include anger, as when one is cut off on the highway by another person, or feeling aroused at the sight of an attractive person. Other examples may include those caused by being on the defencive line and seeing your opponent outweigh you by 40 pounds, and stand 5 inches taller. Before the center hikes the ball he stares at you and says, "I own you. Today you die." Indeed, fear is a powerful basic emotion, as is surprise when you receive the award at a banquet later that year for being the best defensive linesman on the team. The prefrontal lobe seeks to regulate these emotions in a manner consistent with social norms.